Emotions and Family Language Policy: Some Case Studies of Immigrant Families from Europe - Haque, Shahzaman H (2023)
This paper examines the family language policies in five case studies of immigrant families in Europe, focusing on the following emotions: Pride, Joy, Sadness and Fear. Families who immigrated from India and Laos to France, Sweden, Norway and Finland expressed their first and foremost emotions over the maintenance of their heritage languages in terms of language ideologies. The principal purpose of this paper is to explore critically the role of emotions of parents and of children regarding the maintenance or loss of the heritage language and the dominant position that the host language occupies in the framework of the family language policy. With an ethnographic approach, the principal tools were interviews, recording of conversations, participant observations and field notes, which yielded significant information on language attitudes, ideologies and practices toward the host-language and heritage language. Findings show that emotions of anxiety toward enfeeblement of the heritage language were common among parents, albeit not explicitly manifested in some families. Fear of losing the heritage language amounts to fear of losing linguistic and cultural identity over which some parents were frustrated, angry and helpless. Pride and joy were other affective displays, notably related to one’s command of the host languages or powerful languages like English.
Keywords: family language policy; Indian diaspora in Europe; socialisation of emotion; emotions in family language policy; Hmong family in France; case studies from France; Sweden; Norway and Finland; Urdu speakers in Europe